Thermal Management of Electronics : an Experimental Approach Using Phase-Change-Based Materials in Composite Heat Sinks. - Baby, Rajesh (Momentum Press, 2019)
Phase change material (PCM)-based composite heat sinks have attracted great interest in recent decades, especially in the context of thermal management of portable electronic devices such as mobile phones, digital cameras, personal digital assist- ants, and notebooks. In this monograph, a detailed analysis of pinn and metal foam-based heat sinks are presented, based on in-house experiments. Performance benchmarks are articulated and presented for these heat sinks. The state of the art in the development of PCM-based heat sinks and the challenges are outlined, and directions on future development are provided.